2017
DOI: 10.1039/c6ra24847k
|View full text |Cite
|
Sign up to set email alerts
|

Ion-specific ice propagation behavior on polyelectrolyte brush surfaces

Abstract: Ice propagation is an essential step when freezing happens on hydrated surfaces. In this work, we choose polyelectrolyte brushes (PB), whose hydration ability can be controlled by simply exchanging the counterions, to demonstrate the distinct ice propagation mechanism on differently hydrated surfaces.Undesired ice formation on solid surfaces, such as wind turbine blades, power network towers and transmission lines, heat exchanger surfaces and wings of aircra, causes serious property losses and safety risks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…For example, Wang et al revealed that the ions at polyelectrolyte brush interface can effectively control the dynamics of interfacial water and thus determine the ice nucleation and propagation processes. 19,20 Moreover, it was discovered that the ice adhesion strength can be effectively reduced by the aqueous lubricating layer on various hydrated surfaces. 22,31 Ultimately, realizing the regulation of all three aspects of anti-icing with one material simultaneously would require a balance between the optimum structures, mobility, and amount of interfacial water.…”
Section: Progress and Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang et al revealed that the ions at polyelectrolyte brush interface can effectively control the dynamics of interfacial water and thus determine the ice nucleation and propagation processes. 19,20 Moreover, it was discovered that the ice adhesion strength can be effectively reduced by the aqueous lubricating layer on various hydrated surfaces. 22,31 Ultimately, realizing the regulation of all three aspects of anti-icing with one material simultaneously would require a balance between the optimum structures, mobility, and amount of interfacial water.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…17,18 Ion specificity endows polyelectrolyte brushes with unique capabilities of tuning ice nucleation and propagation; however, the poor mechanical robustness limits their application in ice removal. 19,20 Although some hydrated films have ultralow ice adhesion strength due to the aqueous lubricating layer, no excellent anti-icing performance other than reducing ice adhesion has been reported. 21,22 Ideally, an efficient icephobic surface should possess multiple anti-icing features for tackling all the aforementioned obstacles to have true versatility and optimum performance in different possible situations.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Counterions at the ice-substrate interface can also inhibit ice growth by dynamic melting. [39,[171][172][173] Poly([2-(methacryloyloxy)ethyl]trimethylammonium chloride)-Cl (PMETA-Cl) brush was synthesized on silicon wafers, which can accommodate different ions via ion exchange. [171] Brushes with counterions of Cl − , ClO 4 − , PF 6 − , TFSI − , and PFO − were investigated, showing hydrophobicity Cl − < ClO 4 − < PF 6 − < TFSI − < PFO − .…”
Section: Ice Growth Inhibitorsmentioning
confidence: 99%
“…Recently, we investigated the ice propagation behavior on the surface of polyelectrolyte brushes and found that ice propagation can be tuned by changing counterions of the polyelectrolyte brush . However, the exact mechanism for the control of ice propagation remains elusive.…”
Section: Figurementioning
confidence: 99%